PENGARUH SOCIAL NETWORK MARKETING DIMODERASI ROLE OF ECO-FRIENDLY ATTITUDE: CUSTOMER EXPERIENCE DALAM PEMBELIAN KEBERLANJUTAN - Fitri Nuraeni; Ritta Setiyati (JURNAL LENTERA BISNIS, 2023)
There has been a change in people's behavior in shopping for daily needs from offline to online. Along with package delivery services, there has been an increase in plastic waste from package delivery services up to 62% during the pandemic which can threaten environmental health.  This shows a significantly increased consumer awareness of the consumption of environmentally friendly products and indicates the willingness of the domestic market to introduce products that are used sustainably. Get the results that the content hypothesis that comes from social media marketing to sustainable purchases, Customization to sustainable purchases, interactions originating from social media marketing to sustainable purchases and customer experience to sustainable purchases is proven to be significant from the results of data processing and hypotheses. Environmentally friendly consumer attitudes moderate the influence of custumization, environmentally friendly consumer attitudes moderate the influence of word of mouth and environmentally friendly consumer attitudes moderate the influence of trends proven to significantly affect sustainable purchases. Keywords: Social Network Marketing; Role of Eco-Friendly Attitude; Customer Experience; SustainablePurchase.